Doping and cheating in contest-like situations - Matthias Kräkel (Institute for the Study of Labor (IZA), 2006)
Individuals who compete in a contest-like situation (for example, in sports, in promotion tournaments, or in an appointment contest) may have an incentive to illegally utilize resources in order to improve their relative positions. We analyze such doping or cheating within a tournament game between two heterogeneous players. Three major effects are identified which determine a player's doping decision - a cost effect, a likelihood effect and a windfall-profit effect. Moreover, we discuss whether the favorite or the underdog is more likely to be doped, the impact of doping on overall performance, the influence of increased heterogeneity on doping, the welfare implications of doping, and possible prevention of doping.
Keywords: J3; K42; M5; 330; cheating; contest; doping; fraud in research; tournament; Betrug; Professioneller Sport; Drogenkonsum; Wettbewerb; Spieltheorie; Theorie